Analisis Penerapan MOORA Dalam Penyeleksian Peserta Olimpiade Catur dengan Metode Pembobotan Rank Order Centroid - Andreas Gerhard Simorangkir; Kiki Andika; Mesran Mesran (STMIK Budi Darma, 2021)
SMA Negeri 1 Tanjung Morawa is one of the leading public high schools in Deli Serdang Regency which always participates in the Olympics, especially the chess Olympiad. In the selection of Chess Olympiad participants, there are problems. The problem faced in this research is that the principal and teachers at SMA Negeri 1 Tanjung Morawa are still selecting Chess Olympiad participants based only on criteria, namely the accuracy possessed by students, even though there are several criteria that can be considered by the school in selecting students. prospective chess Olympiad participant. These criteria are accuracy, skills, strategy, achievement, class, time, and size. In order to assist the school in selecting prospective chess Olympiad participants, an SPK is needed. The ROC and MOORA methods are one of the methods that can be applied to solve this problem, which can provide assistance to the school in determining the feasibility of selecting chess Olympiad participants. As for the result of the research on the selection of the best Chess Olympiad Participants at SMA Negeri 1 Tanjung Morawa, the best alternative is A22 with a score of 0.244 in the name of